Barriers to Drinking Water Security in Rural Ghana: The Vulnerability of People with Disabilities - Benjamin Dosu; Maura Hanrahan (Water Alternatives, 2021)
Because it is a life-giving substance and one of the crucial components of good health and human survival, access to potable water has been recognised globally as a human rights issue. The current development paradigm also endorses inclusivity in development interventions, calling on leaders of countries to leave no one behind. In most developing countries, however, there seems to be a dilemma as to whether governments can achieve the 'all-inclusive agenda'. Among the most marginalised people are those with disabilities; in terms of access to potable water, this group is likely to face some of the greatest inequalities. Using a qualitative approach that employs in-depth interviews with members of three rural communities in Ghana, this study assesses the water security experiences of persons with disabilities (PWDs). The study identifies barriers such as social exclusion, stigma, distance and water costs, all of which make it difficult for PWDs to collect a sufficient quantity of potable water. Considering the need to achieve universal access to clean water globally, understanding access barriers is essential for rural water management policy decisions. We conclude that in order to enhance access to potable water by PWDs, it is imperative that their needs are assessed, that members of this group are included in rural water management decision-making, and that they are involved in the day-to-day management of drinking water facilities.